Factors Affecting Social Adaptation of Relocated Migrated Households: A Case Study of Duimenshan Resettlement Site in Dongchuan, Yunnan Province, P.R. China - Jianhui, Yun; Kaewtip , Somkid; Panyadee, Chalermchai; Yossuck, Pradtana (Dhammathas Academic Journal, 2023)
Poverty alleviation relocation has greatly improved the social and economic environment ofrelocated migrated households. However, the relocated migrated households, especially those resettled in urban areas, also face a series of economic, social, cultural, psychological and other problems caused by the change of living environment, and their social adaptation at the resettlement site has attracted the attention of all sectors of society. This study, taking Duimenshan resettlement site, a centralized resettlement site of urbanization in Dongchuan, Yunnan Province as a case, aims to investigate the current social adaptation status of relocated migrated households, find out the factors related to their social adaptation, and formulate the appropriate strategies to improve their social adaptation in Duimenshan resettlement site. The selected sample size was 400 relocated migrated households in Duimenshan resettlement site. The structured questionnaire tested by reliability and validity is used for the data collection, and the data were analyzed by using the statistic program for social science research. All factors, including household total annual income, the work experience and physical conditions of the main labor force in human capital, the universality and the high availability of the household’s social network in social capital, the psychological resilience and hope level in psychological capital, as well as the land system and social security system in institutional capital, have a significant impact on the social adaptation of relocated migrated households. The results of the research showed that: 1. The relocated migrated households in Duimenshan resettlement site was at moderate level in economic adaptation and social participation, but high level in cultural assimilation and psychological integration, and the overall social adaptation was at moderate level. 2. Five factors were found to affect social adaptation of relocated migrated households including total annual household income, human capital, social capital, psychological capital, and institutional environment.